Follistatin‐like 1 promotes cardiac fibroblast activation and protects the heart from rupture. Issue 8 (27th May 2016) - Maruyama, Sonomi; Nakamura, Kazuto; Papanicolaou, Kyriakos N; Sano, Soichi; Shimizu, Ippei; Asaumi, Yasuhide; van den Hoff, Maurice J; Ouchi, Noriyuki; Recchia, Fabio A; Walsh, Kenneth
Abstract: Follistatin‐like 1 (Fstl1) is a secreted protein that is acutely induced in heart following myocardial infarction (MI). In this study, we investigated cell type‐specific regulation of Fstl1 and its function in a murine model of MI. Fstl1 was robustly expressed in fibroblasts and myofibroblasts in the infarcted area compared to cardiac myocytes. The conditional ablation of Fstl1 in S100a4‐expressing fibroblast lineage cells (Fstl1‐cfKO mice) led to a reduction in injury‐induced Fstl1 expression and increased mortality due to cardiac rupture during the acute phase. Cardiac rupture was associated with a diminished number of myofibroblasts and decreased expression of extracellular matrix proteins. The infarcts of Fstl1‐cfKO mice displayed weaker birefringence, indicative of thin and loosely packed collagen. Mechanistically, the migratory and proliferative capabilities of cardiac fibroblasts were attenuated by endogenous Fstl1 ablation. The activation of cardiac fibroblasts by Fstl1 was mediated by ERK1/2 but not Smad2/3 signaling. This study reveals that Fstl1 is essential for the acute repair of the infarcted myocardium and that stimulation of early fibroblast activation is a novel function of Fstl1. Synopsis: The secreted glycoprotein Fstl1 is found to be robustly expressed in fibroblasts and myofibroblasts in the infarcted heart. Fstl1 is essential for the acute repair of the infarcted myocardium, and stimulation of early cardiac fibroblast activation is a novel function of Fstl1. Multiple lines of evidence show that cardiac fibroblasts are a major source of Fstl1 production in the injured heart. The major phenotype of fibroblast‐specific Fstl1 deficiency is cardiac rupture and mortality in the myocardial infarction model. Mechanistically, Fstl1 does not directly affect myofibroblast differentiation, but functions at an earlier stage of fibroblast activation, promoting the proliferation and migration of this cell type. Abstract : The secreted glycoprotein Fstl1 is found to be robustly expressed in fibroblasts and myofibroblasts in the infarcted heart. Fstl1 is essential for the acute repair of the infarcted myocardium, and stimulation of early cardiac fibroblast activation is a novel function of Fstl1.